Om Grundtvig, J.A. Möhler og romantikken - Michelsen, William (Grundtvig-studier, 1996)
About Grundtvig, J.A. Möhler and Romanticism By William Michelsen William Michelsen criticizes William Franklin’s comparison of Grundtvig and Möhler, published in this volume of Grundtvig Studies. In William Michelsen’s opinion, it is misleading to assume that Grundtvig’s theology came about under the influence of the German philosopher Schelling, and subsequently to infer a common point of departure for Grundtvig and Möhler. Grundtvig’s attitude to German Idealism in general and Schelling’s philosophy in particular is one of unmitigated repudiation.